Performance measure of eco-process innovation: Insights from a literature review - Suziyana, Mat Dahan; Sha'ri, Mohd Yusof; Mohd Yusof, Taib (EDP Sciences, 2017)
Eco-process innovation has been recognised as one of the important strategies for mitigating the growing environmental challenges. Its concept has succeeded in drawing the interests of many scholars worldwide. The aim of this paper is to review the literature to clarify how one actually measure eco-process innovation performance. Critical analysis of literature has been performed in this study. Database searches were mainly relied to compile the literature. In relation to eco-process innovation assessment, results revealed that most prior works focused on the economic and environmental performance with the exclusion of social performance and very limited attempts done in analysing real operational data. It was identified that there is a need for empirical investigations on measuring the social performance of eco-process innovation along with the economic and environmental performance, and on development of operational measuring instrument as these study area have not been well explored.